1991 annual report - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 1991)
This progress report is for the period February 1990 - July 1991 for the Central Plains Experimental Range long term ecological research project at Colorado State University. Our previous report was included with our 1990 renewal proposal.
Progress report
SGS-LTER 1991 annual report
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: shortgrass steppe; Central Plains Experimental Range; Pawnee National Grassland; grassland ecology; long term ecological research